The use of media resources in foreign language studies in Kazakhstan - Rahila Aubakirova, Bakyt Kuanysheva,; Zhukenova, Alma; Dmitrii V. Enygin, Nataliia Yu. Fominykh, (Opción, 2019)
This article analyzes the features of the construction of educational programs in higher vocational schools, examines the specifics of the use of media resources in the study of a foreign (English) language via comparative qualitative research methods. As a result, the process of learning a foreign language involves interacting with other people, working in a group, and participating in collective activities. In conclusion, when changes occur in education, the pedagogical system adapts to them in order to provide solutions that improve the teaching experience and practice of learning activities.